STUDI MENGENAI EXPERIENTIAL MARKETING DAN PENGARUHNYA TERHADAP EXPERIENTIAL VALUE DAN CUSTOMER SATISFACTION PADA MAXX COFFEE - Anthony Sadeli; Ari Setiyaningrum (Prosiding Working Papers Series In Management, 2018)
This research aims to analyze the effect of experiential marketing dimensions namely sense perception, feel perception and think perception on experiential value as well as customer satisfaction of Maxx Coffee’s consumers. The sampling method that used in this research is non-probability sampling using the convenience sampling technique. 120 consumers of Maxx Coffee participated as the respondents. Multiple regression analysis with SPSS 23 software used in this research to analyze the data. This research indicated that sense perception have no significant effect on experiential value while feel perception and think perception have a significant effect on experiential value. This research also indicated that sense perception, feel perception and think perception have a significant effect on customer satisfaction.Keywords : sense perception, feel perception, think perception, experiential value, customer satisfaction